Prelimenary Modeling for Assessing Tidal Stream Energy Potential at the Alas Strait, Indonesia - Mukhtasor Mukhtasor; Luli Bangkit Sugito; Sujantoko Sujantoko (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2017)
This study is on ocean current prelimenary modelling in Alas Strait, Indonesia, to be compared with the field observation data. The model maps coordinate for ocean current so that the potential energy resource can be identified. The model simulation is established with two different scenarios; the first scenario is using windspeed factor and the second without using that factor. Complementary variables such as bathymetry, water elevation, bottom friction, and eddy viscosity have the same value for both scenarios. This ocean current modelling use finite element method with flexible mesh. This method use two dimension numerical solution from the average incompressible Reynolds Navier – Stokes equation with the assumption from Boussinesq dan hydrostatic pressure. This model consists of continuity equation and momentum which closed by turbulen scheme. This study concludes the first scenario is a success and valid with the water surface elevation mean error is 4.2% and water current speed mean error is 10.7%. The second scenario is unseccesful as indicated by the water surface elevation mean error of 13.4% and the water current speed mean error of 11,7%, and also the phase and the trend of current speed is verging the field observation data.